Advanced visual slam and image segmentation techniques for augmented reality - Jiang, Yirui; Tran, Trung Hieu; Williams, Leon (IGI Global, 2022)
Augmented reality can enhance human perception to experience a virtual-reality intertwined world by computer vision techniques. However, the basic techniques cannot handle complex large-scale scenes, tackle real-time occlusion, and render virtual objects in augmented reality. Therefore, this paper studies potential solutions, such as visual SLAM and image segmentation, that can address these challenges in the augmented reality visualizations. This paper provides a review of advanced visual SLAM and image segmentation techniques for augmented reality. In addition, applications of machine learning techniques for improving augmented reality are presented.
Keywords: Augmented reality; computer vision; image segmentation; machine learning; visual SLAM